Refractory Hyponatremia on Therapy in Syndrome of Inappropriate Antidiuretic Hormone: A Case Report - Roat Yeti Mustafida; Nabilah Puspa Utami; Mohammad Zakaria Shahab; Yohana Sahara (Jurnal Multidisiplin Madani, 2022)
Hyponatremia is particularly common in neurosurgical patients, occurring in up to 50% of cases depending on the underlying diagnosis. One of the causes is the syndrome of inappropriate antidiuretic hormone (SIADH). Treatment for this condition mainly increases sodium intake and fluid restriction. Both of these therapies are potentially dangerous in some cases. Thus the therapy should be considered thoroughly. In this case we present, A 33-years-old male with refractory hyponatremia day-8 post craniotomy. Serum sodium was measured after every treatment. The patient was given hypertonic saline, fluid restriction advice, and a combination of those treatments. Yet every treatment gave various outcomes. Although the theory was put into practice, therapy in SIADH is harder than expected due to variations in the patient’s condition